Argumentacja bioetyczna w rozumowaniu prawniczym - Królikowski, Michał (Wydział Teologiczny, UAM, 2011)
Ethical argumentation pertaining to the protection of human life and dignity is certainly present in legal reasoning. The latter, seeking credibility, adopts constructions which are intuitively or culturally accepted as capable of justifying answers to arising dilemmas. Law makes use of bioethical argumentation in various ways and rather eclectically. The author presents three basic forms assumed by relations between law and ethics - interpretation of notions, figures of responsibility, reconstruction of protected goods. Detailed grounds of legal decisions are discussed as a background for the ethical issues involved.
Bioethical Argumentation in the Legal Reason
Keywords: prawo; law; etyka; ethics; argumentacja; argumentation; odpowiedzialność; responsibility; życie i zdrowie ludzkie; human life and health